Reverse redrawing of cups using a flexible tooling - Li, Bin. (2008)
This report presents the principle of reverse redrawing of cups at a high redrawing ratio using an annular urethane pad. The study of the parameters includes annealing conditions of the first stage cups, dimensions of the urethane pad, compression ratio of urethane pad, dimension design of drawing die and the effect of lubrication. The reverse-redrawing tooling with guide pin, guide bushing and urethane pad, which is modified, have been designed, fabricated, and tested. The experimental test process for the first stage cup of 100mm diameter at drawing ratio 1.7 is carried out from a blank of 170mm diameter. The reverse redrawing tooling is successfully accomplished at redrawing ratio of 2.94. During the process, the effect of annealing condition at 400°C and 500°C for both one and two hours is investigated. The introduction of a stepped diameter on the urethane pad greatly improves the draw ability. Lubricant with high viscosity proves to be effective as the lubricating agent between the die and first stage cup. Based on the experiments, the optimum redrawing conditions are successfully determined at the redrawing ratio of 2.94.